(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to compare the diagnostic accuracy of transvaginal sonography and saline infusion sonography in the detection of intracavitary space-occupying lesions (endometrial polyp and submucous fibroid) in infertile women.Material and Methods: Three hundred and twenty-three women with infertility were involved in this retrospective study. The diagnostic accuracy of transvaginal sonography and saline infusion sonography were compared with respect to evaluation by diagnostic hysteroscopy results. The sensitivity, specificity, predictive values and ROC curves were used to determine the efficacy of methods for detecting the intracavitary space-occupying lesions in infertile patients.Results: The incidence of intracavitary space-occupying lesions was 82.1% infertile women. The endometrial polyp and submucous fibroid were established in 56 (17.3%) and 5(1.5%) patients, respectively. The sensitivity and specificity of transvaginal sonography were 50.8% and 98.1%, respectively. These values were 80.3% and 98.5% for saline infusion sonography, respectively. Saline infusion sonography was found superior to transvaginal sonography for evaluating the intracavitary space-occupying lesions.Conclusion: Saline infusion sonography was more accurate diagnostic modality than transvaginal sonography to assess the intracavitary space-occupying lesions in the infertility population. Therefore the addition of saline infusion sonography to the infertility workup may prevent unnecessary invasive procedures to evaluate the uterine cavity.